Member • Jan 11, 2014

RajniWhere is the mistake in the below explanation?

Administrator • Jan 11, 2014
'x = y' , which means Apple = Orange.Are you sure? This action cannot be undone. 
Member • Jan 11, 2014
It's actually
3*0 = 0Are you sure? This action cannot be undone. 
Member • Jan 11, 2014
Right.Anoop KumarIt's actually 3*0 = 0
The last but one step can be elaborated as 3 x 0 = 1 x 0. The fallacy is that dividing both sides by zero gives 3 = 1.
Dividing by zero is an invalid operation.Are you sure? This action cannot be undone. 
Member • Jan 12, 2014
Check step number 5:
it goes as 3X=X = 3Y = Y
is this supposed to be 3XX = 3Y  Y ?
if it is, then the mistake occurs at step number 6.
Step number 6 would correctly go as : 3X  3Y = Y  XAre you sure? This action cannot be undone. 
Member • Jan 12, 2014
1=3 is incorrect equationAre you sure? This action cannot be undone. 
Administrator • Jan 12, 2014
The first line itself is wrong. When you say, 'x=y', which means 'x' and 'y' are one and the same thing. So it can be extended to any level and prove anything equal to anything.Are you sure? This action cannot be undone. 
Member • Jan 12, 2014
yesKaustubh KatdareThe first line itself is wrong. When you say, 'x=y', which means 'x' and 'y' are one and the same thing. So it can be extended to any level and prove anything equal to anything.Are you sure? This action cannot be undone. 
Member • Jan 14, 2014
Not really. X can be the number of girls in a class while y can be the number of desks in the class. The real issue is that division by zero is not a defined mathematical operation. The whole thing is set up as a confusing buzz, hiding the wrong operation.micheal johnyesAre you sure? This action cannot be undone. 
Member • Jan 17, 2014
step1: x=y
but in step5, 3(xy)=(xy)
which means, 3(0)=(0)
the mistake occurs here..😎Are you sure? This action cannot be undone. 
Member • Sep 15, 2014
A.V.RamaniRight.
The last but one step can be elaborated as 3 x 0 = 1 x 0. The fallacy is that dividing both sides by zero gives 3 = 1.
Dividing by zero is an invalid operation.
Sir nailed it. Simple and elegant explanation.Are you sure? This action cannot be undone. 
Member • Sep 16, 2014
The above thing is just like.....
If a=b , b=c then a=c
Implies 2=root(4) , root(4)=2 then 2=2Are you sure? This action cannot be undone. 
Member • Sep 16, 2014
Not really.shiwa436The above thing is just like.....
If a=b , b=c then a=c
Implies 2=root(4) , root(4)=2 then 2=2
In maths there is an equality and there is an identical equality.
Both +2 and 2 are roota of 4.
So 2 = Sqrt(4) does not mean 2 is identically equal to Sqrt(4)Are you sure? This action cannot be undone. 
Member • Sep 16, 2014
#LinkSnipped# ramani.. Sir,
A small explanation will convince us, both the things are just outta incomplete application of actual rules....Are you sure? This action cannot be undone. 
Administrator • Sep 16, 2014
This is the simplest explanation:
The 'proof' starts by assuming 'X' = 'Y'. Since X and Y aren't defined > you should be able to prove almost anything; because it's based on 'assumption' that X = Y.Are you sure? This action cannot be undone. 
Member • Sep 16, 2014
Sqrt(4) = +/ 2shiwa436#LinkSnipped# ramani.. Sir,
A small explanation will convince us, both the things are just outta incomplete application of actual rules....
Using Sqrt(4) to mean +2 in one part of the argument and 2 in another part leads to an inconsistency beca
The original problem has a different issue. That argument uses division by zero, which is not permitted in maths.Are you sure? This action cannot be undone. 
Member • Sep 17, 2014
The problem is not the assumption. Mathematics gives us the full liberty to assume anything that fits the rules (and here assuming two variables are equal is not against any). The problem is the step (tricky step) which is so common to many such "proofs" which claim flabbergasting results to be true. This tricky step is intentionally introduced because it skips the attention of most amateur proof readers: and the step is called "division by zero", which is not defined.Kaustubh KatdareThis is the simplest explanation:
The 'proof' starts by assuming 'X' = 'Y'. Since X and Y aren't defined > you should be able to prove almost anything; because it's based on 'assumption' that X = Y.Are you sure? This action cannot be undone. 
Member • Nov 26, 2014
below the 4th dotRajni JainWhere is the mistake in the below explanation?
Are you sure? This action cannot be undone.